Associations between the neighbourhood environment characteristics and physical activity in older adults with specific types of chronic conditions: the ALECS cross-sectional study - Barnett, Anthony; Cerin, Ester; Zhang, Casper J. P.; Sit, Cindy H. P.; Johnston, Janice M.; Cheung, Martin M. C.; Lee, Ruby S. Y. (The international journal of behavioral nutrition and physical activity, 2016)
Neighbourhood characteristics may influence physical activity (PA), which has positive effects on the health of older adults. Older adults with chronic conditions are less active and possibly more affected by environmental factors than their peers. Understanding neighbourhood characteristics associated with PA specific to older adults with chronic conditions is currently lacking. This cross-sectional study aimed to assess the associations between the neighbourhood environment and various forms of PA in older adults with and without visual impairment, hearing impairment, musculoskeletal disease and/or genitourinary disease. Neighbourhood environment and PA data were collected in Hong Kong older adults (N = 909) from 124 preselected neighbourhoods stratified for walkability and socioeconomic status. Generalized linear models and zero-inflated negative binomial models with robust standard errors were used to examine associations of perceived neighbourhood environment characteristics, and the moderating effects of having specific chronic conditions, with PA outcomes. Thirteen perceived neighbourhood characteristics were associated with older adults' PA in the expected direction irrespective of their health condition. Nine neighbourhood characteristics had associations with PA that were dependent on hearing impairment, vision impairment, musculoskeletal disease or genitourinary disease. In general, they were stronger in participants with than without a specific chronic condition. Maximizing the potential for PA in older adults who have lower levels of physical functionality due to chronic conditions may require neighbourhood characteristics specific to these groups.